Innovative Surgical Treatment of Cerebral palsy (KYAMC Journal, 2021)
Cerebral palsy means partial brain paralysis, like facial palsy where facial nerve is paralyzed. It is mainly due to birth induced asphyxia others a lot of causes also present. Convulsion is most common symptoms of cerebral palsy. This convulsion leads to further hypoxia which leads to further brain damage. Indirectly it is permanent and progressive disorder. Ultimately patient is unable to walk, communicate and perform normal life. Birth asphyxia leads to hyperostosis of skull bone. Premature closure of sutures specially fontanelle. Early closure of sutures of skull and fontanelle. At the same time temporal fossa is small and commonly temporal bone thickened excessively as a sequalae total intracranial volume decreased and which restrict to expansion of brain uniformly. As the age advances simultaneously brain also increase at its maximum level up to 5 years but rigid skull doesn’t allow the expansion of brain due to early closure of suture .and excessive growth of bones even in skull base. Temporal bone also exceptionally thickened. Normal as usual treatment failed to cure cerebral palsy patients. This new cranial vault reorganization or reconstruction by Bilateral cranioplasty and duraplasty giving surprising result of these cerebral palsy patients. This case hase been operated in Khwaja Yunus Ali Medical College and Hospital, Enayethpur, Sirajganj, Bangladesh. Patient’s appearance become quite normal just after operation.KYAMC Journal.2021;12(1): 56-59